Corporate Social Responsibility PT. Pertamina Case Study: Gerakan Menabung Pohon - Ermasari, Elisa; Rudito, Bambang (Journal of Business and Management, 2014)
Indonesia is one of the countries that have the largest number of forest in the world. Indonesia had previously been named by the United Nations to be one of the largest oxygen producing countries in the world and into the lungs of the world. But now Indonesia has lost a lot of their forest. This was shown by the destruction of forests across Indonesia, and make Indonesia as one of the countries that has the fastest deforestation in the world. Global warming is one of the major problems that must be faced by all people in the world. Therefore PT. Pertamina seeks to find solutions to these problems and create a CSR (Corporate Social Responsibility) that aims to reduce the effects from global warming that has been faced by the world residents. Corporate social responsibility program from PT. Pertamina. This program is aimed to reduce the effects of global warming and want to improve the welfare of the people in East Lombok to check this program has been running smoothly or not, The author will analyze the relationship between each of the parties involved in implementing the